Alternative activation generates IL-10 producing type 2 innate lymphoid cells. Issue 1 (December 2017) - Seehus, Corey; Kadavallore, Asha; Torre, Brian; Yeckes, Alyson; Wang, Yizhou; Tang, Jie; Kaye, Jonathan
Abstract Type 2 innate lymphoid cells (ILC2) share cytokine and transcription factor expression with CD4+ Th 2 cells, but functional diversity of the ILC2 lineage has yet to be fully explored. Here, we show induction of a molecularly distinct subset of activated lung ILC2, termed ILC210 . These cells produce IL-10 and downregulate some pro-inflammatory genes. Signals that generate ILC210 are distinct from those that induce IL-13 production, and gene expression data indicate that an alternative activation pathway leads to the generation of ILC210 . In vivo, IL-2 enhances ILC210 generation and is associated with decreased eosinophil recruitment to the lung. Unlike most activated ILC2, the ILC210 population contracts after cessation of stimulation in vivo, with maintenance of a subset that can be recalled by restimulation, analogous to T-cell effector cell and memory cell generation. These data demonstrate the generation of a previously unappreciated IL-10 producing ILC2 effector cell population. Type 2 innate lymphoid cells (ILC2) are thought to be a uniform population of effector cells that produce IL-5 and IL-13. Here, the authors shown that, in mice, IL-33 can alternatively activate these cells to generate a molecularly distinct IL-10-producing subset designated ILC210 .